Re-Evaluating the Development of the Islamic Sciences: The Case Against the Classical Narrative and the Myth of Decline - Lucas, Adam (Universitas Islam Indonesia, 2024)
Eurocentric myths about Western scientific and technological superiority persist in popular culture and some scholarly circles. A prevalent myth suggests that Islamic contributions to modern science were primarily the transmission of ancient Greek and Roman knowledge to medieval and early modern Europe. A less extreme version posits significant contributions during Islam's